A Comparative Study on the Occurrence of Cor Pulmonale among the Cases of COPD and Bronchial Asthma - Ekram, ARM Saifuddin; Hasan, AM Shafiqul; Haque, M Monzurul; Ahsanullah, AZM; Islam, Q Tarikul; Azhar, M Abu; Islam, M Fakrul (TAJ: Journal of Teachers Association, 2011)
This hospital-based study was carried out on the patients of chronic obstructive pulmonary diseases (COPD) and bronchial asthma, who were admitted into the Department of Medicine, Rajshahi Medical College Hospital between the period of July 1999 to December 2000. The main objective of the study was to compare the occurrence of cor pulmonale among the patients of COPD and bronchial asthma. Sixty patients fulfilling the diagnostic criteria of bronchial asthma (n=30) and COPD (n=30) from the admitted cases of obstructive air way diseases were included in the study by random sampling method. It was found that occurrence of cor pulmonale was significantly higher among the patients of COPD than those of bronchial asthma. DOI: http://dx.doi.org/10.3329/taj.v14i2.8386 TAJ 2001; 14(2): 56-60